Plant Identification in the Closed-loop Control System; Lecture Notes in Engineering and Computer Science; Vol. 1 : Proceedings of the International MultiConference of Engineers and Computer Scientists 2016. IMECS 2016, 16-18 March, 2016, Hong Kong - Krinicin N. S. Nikolay Stanislavovich; Uvarova A. D. Anastasiya Dmitrievna; Dyadik V. F. Valery Feodosievich; Goryunov A. G. Aleksey Germanovich; Nadezhdin I. S. Igor Sergeevich (2016, 2016)
Title screen